FENOMENA JILBAB DALAM MASYARAKAT KOSMOPOLITAN: INTERPRETASI TEKS DAN KONTEKS ATAS AYAT JILBAB - Yulia Hafizah (UIN Antasari Banjarmasin, 2018)
This paper aims to reveal the various interpretations of ulama to the meaning of the veil text. Then try to bring that understanding to the current development context. This paper is the result of literature research (library research) which is arranged in the form of papers. Data mining is carried out by exploring various sources that are relevant to this research, namely reviews from the mufassir, both classical and contemporary related to the veil verse in Alquran, namely Q.S. al-Ahzab: 59 and an-Nûr: 31, then compiled and read with a historically critical approach. This paper shows that the various ideas of classical and contemporary ulama are inseparable from the social context of their time. This social context ultimately makes the veil no longer just a symbol of identity, but more than that. The appearance of various hijab communities which later formed a new social movement has brought modern value in lifestyle and opened opportunities for the development of new sectors in the economy.